Cowgirl dreams : a western childhood - Dewey, Jennifer (Honesdale, PA : Boyds Mills Press, 1995)
The author recalls her childhood memories of living on a ranch in New Mexico.
Keywords: Cowgirls -- New Mexico; Ranch life -- New Mexico; Swine -- New Mexico; Ranch life -- New Mexico; Pigs as pets; Family life -- New Mexico